Peningkatan Kinerja Teknologi Pendidikan dan Penerapannya pada Pembelajaran Pendidikan Agama Islam - Agus Ali; Erihadiana Erihadiana (Jurnal Dirosah Islamiyah, 2021)
The use of technology has a positive and negative impact in the world of education. The positive impact, among others, is to make it easier for teachers to deliver material in a way that is no longer manual. By using technology, we can also provide a more concrete picture when conveying material about something. And another impact is that it can make it easier for us to process information, for example by using the internet. The negative impacts of using technology in education include, among others, the existence of technical disturbances that make the learning process disrupted. In this case, it turns out that the technology we use is no longer helpful. For example, if in the learning process that utilizes the LCD suddenly the power goes out, it will be difficult for us to convey the material that has been prepared (Susilana & Riyana, 2008). Another negative impact is, due to technological advances, individuals tend to be individualistic and less social in life. And sometimes some individuals often misuse technology, thus wasting their time with activities that are less useful.